Nowe trendy w teoriach rozwoju karier – implikacje dla poradnictwa kariery - Solarczyk-Ambrozik, Ewa (Wydawnictwo Naukowe UAM, 2015)
The article is concerned with transformations of career models, their theoretical explications as well as social methods aimed at solving problems in this area, becoming part of career counselling and mentioned in terms of broader transformations, mainly changes in the sphere of work and the postmodern vision of the world. Detailed analyses deal with new trends in career development theories and they were conducted on the basis of the review of dominant career theories and their implications for counselling methods. Paradigm shifts have been presented, from dominant quantitative approaches to a feature and a factor up to constructivist approaches, thus illustrating new conceptualizations of work life and paradigm shifts in the field of career counselling. Detailed problems shown in the article concern mainly the cultural accuracy of the career counselling theory and methods, the necessity for diversification of research methods concerning careers and their development determinants, integration and convergence of various career theories or diversification of counselling methods.
New Trends in Career Development Theories: Implications for Career Counselling
Keywords: career development theories; convergence of career theories; career planning; career counselling; paradigm shift; career models; counselling theory and methods indigeneity; culturally sensitive methods